Pembentukan Komunitas Virtual di Platform X: Studi Kasus Reaksi Komunitas Marah-Marah Atas Penganugerahan Gelar H.C. Kepada Raffi Ahmad - Anahiz, Sarah; Hakim, Syiefa Alaida; Ramadhan, Muhammad Fitra Aulia; Azhari, Shinta Dwi; Ilham, Muhammad Fakhriansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The conferral of this honorary title has sparked mixed reactions from the public, particularly on social media platforms, where diverse opinions are widely expressed. One of the most vocal groups is the virtual community known as the